2022
DOI: 10.3390/life12101676
|View full text |Cite
|
Sign up to set email alerts
|

Distinguished Functions of Microglia in the Two Stages of Oxygen-Induced Retinopathy: A Novel Target in the Treatment of Ischemic Retinopathy

Abstract: Microglia is the resident immune cell in the retina, playing the role of immune surveillance in a traditional concept. With the heated focus on the mechanisms of microglia in pathological conditions, more and more functions of microglia have been discovered. Although the regulating role of microglia has been explored in ischemic retinopathy, little is known about its mechanisms in the different stages of the pathological process. Here, we removed microglia in the oxygen-induced retinopathy model by PLX5622 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For microglia removal, colony-stimulating factor 1 receptor (CSF1R) inhibitor PLX5622 (Selleck, Shanghai, China) was given daily with oral gavage to OIR mice from P12, as described before. Pups were anesthetized and killed at P17 [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For microglia removal, colony-stimulating factor 1 receptor (CSF1R) inhibitor PLX5622 (Selleck, Shanghai, China) was given daily with oral gavage to OIR mice from P12, as described before. Pups were anesthetized and killed at P17 [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the intravitreal injection of bone marrow-derived M2 macrophages promoted pathological retinal angiogenesis [ 134 ]. PLX-5622 -mediated microglia depletion reduced pathological angiogenesis in OIR [ 135 ]. Systemic macrophage depletion with intraperitoneal clodronate liposomes reduced retinal avascular area and neovascular tufts at P17 after OIR [ 136 ].…”
Section: Myeloid Cells In Retinal Pathological Angiogenesismentioning
confidence: 99%
“…Similarly, several retinal degenerative diseases associated with elevated GFAP and Müller cell gliosis, including light-induced retinal degeneration, are also associated with increased Gal3 expression [5,101]. Gal3 knockout significantly dampened the reactivity of glial cells and preserved photoreceptor cells and ganglion cells [71,109]. Therefore, it could be concluded that in the absence of Gal3, a mere 30% decrease in cerebral blood flow itself would not result in any significant retinal damage.…”
Section: Retinal Degenerative Diseasementioning
confidence: 99%